Degree of cognitive impairment in patients with carotid stenosis in relation to cerebral ischemic lesions - Joveva, Elena; Djordjević, Gordana; Milošević, Vuk; Arsovska, Anita; Živković, Miroslava (Vojnosanitetski pregled, 2022)
Background/Aim. Carotid stenosis is a risk factor for cognitive impairment. The aim of the study was to evaluate the degree of cognitive impairment in patients with asymptomatic and symptomatic carotid stenosis and correlate it with the presence, location, and extent of cerebral ischemic lesions. Methods. A prospective analysis of 180 patients aged 50–70 years, divided into three groups (asymptomatic carotid stenosis, symptomatic carotid stenosis, and controls) was made. We assessed demographic characteristics, vascular risk factors, ultrasound examination of the carotid arteries, computerized tomography (CT), magnetic resonance imaging (MRI) of the brain, and neuropsychological testing. Results. The brain CT findings on admission showed ischemic lesions in the left hemisphere in 13.3% of patients in the asymptomatic group and in 41% of those in the symptomatic group. In the right hemisphere, lesions were registered in 10% of the asymptomatic patients and in 46.7% of the symptomatic patients.  The difference between groups was statistically significant. The lesion volumes measured on CT and MRI scans were significantly different (p < 0.001) between groups with asymptomatic and symptomatic carotid stenosis. The degree of cognitive impairment, measured by the Addenbrooke's Cognitive Examination Revised (ACE-R), was significantly different between the groups (p
Keywords: cognition disorders; carotid stenosis; diagnosis; magnetic resonance imaging; severity of illness index; risk factors; x-ray computed tomography